PENGARUH KOMUNIKASI INTERPERSONAL GURU PENDIDIKAN AGAMA ISLAM DAN MOTIVASI TERHADAP PRESTASI BELAJAR SISWA - Muhtadin, Muhtadin (Universitas Prof. Dr. Moestopo (Beragama), 2018)
This study aims to discuss the interpersonal communication interactions of PAI teachers and learning motivation towards the learning achievement of PAI students. Madrasah Aliyah Nurul Islam empties Boyolali in the academic year 2017/2018.The results of the analysis show that (1) There is a significant effect between PAI interpersonal communication and learning achievement. This can be seen from the results of t-count of -2.302> t-table -2,021. This is also corroborated by the significant value of Interpersonal Communication of 0.026. Because the significance value is 0.026 <0.05, it can be concluded that there is a relationship between the variables of Interpersonal Communication on Student Learning Achievement. (2) There is a significant influence between motivation and learning achievement. This can be seen t-count -2.111> t-table -2.021. Because the value of t-count> t-table is -2.111> -2.201, then motivation has competence in PAI students' learning achievement. This is also corroborated by the significant motivation value of 0.026. Because the significance value is 0.040 <0.05, it can be concluded that there is a variable influence on Student Learning Achievement. (3) There are interactions between interpersonal teachers of PAI communication and motivation together (simultaneous) with learning achievement. From the results of data processing can be obtained R² value of 0.386 So Interpersonal Communication and Motivation Increases learning achievement by 38.6%, while the remaining 61.4% is needed by other variables outside of this study.